Lived Experiences, Academic Performance, and Aspirations of a Muslim Learner in a Public High School (International Journal of Scientific Research and Management (IJSRM), 2021)
This study was conducted to narrate the experiences, academic performance, and aspirations of a Muslim learner in a public high school. The findings of the study served as the basis for understanding the learning situation and performance of the learner. Specifically, this study sought to: describe the living condition of the Muslim learner in terms of family income and size and how these affected her academic performance; discuss the aspirations, experiences, and challenges of the Muslim learner in a public high school; and describe the academic performance of the Muslim learner during her stay in a public high school. The researcher employed the qualitative research design, particularly the case study method of research. The researcher, later on, came up with themes to describe the experiences and performance of the Muslim learner and a recommendation for future research was also made by the researcher. These were the themes presented in this paper: (1) Experiences in a public high school. (2) Quality of education. (3) Family support. (4) Academic performance. (5) Dreams and aspirations. It can be noted that the respondent had positive experiences in her stay in a public high school. She did not feel any discrimination and untoward incident of her being a Muslim. However, she pointed that she would have wanted to have Muslim teachers or included in the curriculum will be lessons specifically for them, as specified in Madrasah education. She had struggled a lot, though, in her academic performance, because of difficult situations she had experienced.